Psychological and somatic distress in Chinese outpatients at general hospitals: a cross-sectional study - Xiong, Nana; Schäfert, Rainer (Annals of general psychiatry, 2017)
Our study aimed (1) to describe the proportion of psychological distress among Chinese outpatients at general hospitals, (2) to compare cognitive and behavioral characteristics of patients with different distress patterns, and (3) to investigate the discriminant function of the analyzed variables in indicating the affinity towards the different distress patterns.
Gesehen am 25.10.2018